2007
DOI: 10.1080/17441690600648728
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of women seeking medical care for obstetric fistula in Eritrea: Implications for prevention, treatment, and social reintegration

Abstract: This article presents findings from qualitative interviews with women seeking medical care for obstetric fistula in Eritrea. The interviews were designed to inform programme design for the prevention and treatment of obstetric fistula. Interviews were conducted with 11 new fistula repair patients, 15 women returning for follow-up for their fistula repairs, and five accompanying family members at Massawa Hospital in the Northern Red Sea Zone of Eritrea during November-December 2004. The women described long del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(43 citation statements)
references
References 7 publications
2
31
1
Order By: Relevance
“…All included studies were conducted in Sub-Saharan Africa: two in Ethiopia [21, 22], five in Tanzania [11, 13, 23–25], one in Uganda and Tanzania [11], one in Eritrea [16], two in Uganda [26, 27] two in Nigeria [19, 28], one in Kenya [29],one in Ghana [30], and one in Malawi [31]. All research took place in treatment or rehabilitation facilities, except reports from Kenya and Malawi which were conducted in the community.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All included studies were conducted in Sub-Saharan Africa: two in Ethiopia [21, 22], five in Tanzania [11, 13, 23–25], one in Uganda and Tanzania [11], one in Eritrea [16], two in Uganda [26, 27] two in Nigeria [19, 28], one in Kenya [29],one in Ghana [30], and one in Malawi [31]. All research took place in treatment or rehabilitation facilities, except reports from Kenya and Malawi which were conducted in the community.…”
Section: Resultsmentioning
confidence: 99%
“…Physical consequence was the core theme shared across most studies, described as loss of body control and the challenges faced to keep cleanness [13, 16, 19, 24, 28, 29, 32]. Physical challenges include the emotional and medical problems of fistula which resulted from incontinence, such as genital sores, smells, wounds, pain, discomfort, exhaustion, and foot drop [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Published accounts have found that many women and their families fail to recognise danger signs that necessitate skilled attendance at delivery or experience delays in seeking care due to lack of transportation or funds for transport; some experience delays once they reach the facility due to lack of providers, supplies, or equipment (Bangser et al, 2010; Holme, Breen, & MacArthur, 2007; Mselle, Kohi, Mvungi, Evjen-Olsen, & Moland, 2011a; Turan, Johnson, & Polan, 2007). …”
Section: Introductionmentioning
confidence: 99%
“…Awareness of obstetric fistula is still low in many developing countries where it is prevalent [23]. In Uganda, an estimated 2.6% (about 142,000 women) of reproductive age nationally have experienced obstetric fistula [22].…”
Section: Introductionmentioning
confidence: 99%